Study on the basic properties and mechanism of waste sludge solidified by magnesium phosphate cement containing different active magnesium oxide. (26th April 2021) - Peng, Lei; Chen, Bing
Highlights: Magnesium oxide with different activities and their combination were used to solidify the sludge. The retarders and low-activity magnesium oxide reduced the reaction rate and increased the strength. The spontaneous imbibition height considering the different arrangements of triangles and hexagons were derived. The water resistance and shrinkage mechanism of the cured body were analyzed. Abstract: Magnesium phosphate cement (MPC) containing different active magnesium oxides was used to solidify waste sludge. The fluidity, setting time, unconfined compressive strength, water resistance, shrinkage deformation, spontaneous imbibition, water absorption, thermal conductivity, leachate and particle shape and arrangement of the solidified body were studied and evaluated. Results showed that MPC can be used as a fast sludge curing agent. When the ratio of dead burnt magnesia to light burnt magnesia was 3:7, the strength was the highest. This suggested that appropriately reducing the reaction rate can quantitatively adjust struvite crystals and increase strength. The retarder reduced the reaction rate and increased the strength, which indirectly indicated that the strength was affected by the rate of formation of hydration products. The shrinkage mainly came from the dry shrinkage induced by the evaporation of water, the conversion of free water in the reaction into the bound water in the crystal, and the shrinkage induced by the heat released by the acid-base neutralization reaction. The unsaturated imbibition was mainly divided into the rapid imbibition stage, the unsteady imbibition stage and the equilibrium zone. Imbibition indexes have a linear relationship with the square root of time. For spontaneous imbibition height: the arrangement of regular hexagonal particles ≤ triangular arrangement < spherical arrangement. The equivalent diameters of different particle shapes and the corresponding pore shape correction factors were derived. This study provided a scientific basis for the feasibility of solidified waste sludge as a slope protection, landfill and sustainable green building material.